Anemia por deficiência de B12: revisão de literatura - Bezerra, Marjory Sandra de Lima (2024)
Vitamin B12 also called cyanocobalamin or cobalamin, is essential for neural function, acting on the maturation of red blood cells and as a cofactor in the body's reactions. Thus, to be absorbed it is necessary that it be combined with the intrinsic factor, produced by the parietal cells of the stomach. Its sources of obtaining through the diet, involves the intake of red meat, fish and crustaceans, eggs, milk and cereals. Thus, vitamin B12 deficiency is one of the most common causes of megaloblastic anemia, more specifically pernicious anemia. This study is a literature review, which aims to address, understand and identify relevant aspects of cobalamin deficiency and its impact on the lives of patients with this condition. A data analysis was carried out in the period from January to July 2024, with an active search for keywords on the subject and after reading and filtering, the main information was grouped in the form of this review that highlighted the deficiency occurrence due to four primary etiologies, involving autoimmune disease, malabsorption, insufficient diet and exposure to nitrous oxide. Vitamin B12 deficiency is defined as cobalamin levels lower than 148 picomol per liter (pmol/L) or 200 nanograms per deciliter. This depletion leads to the appearance of clinical manifestations characterized by hematological, immunological and neurological changes. Thus, upon clinical suspicion, blood count, serum dosage of vitamin B12 and folate should be requested for initial diagnosis. And, for complementation and differentiation between pernicious anemia and respective differential diagnoses, it is also necessary to request autoantibodies intrinsic anti-factor and anti-parietal cells. Regarding the laboratory findings, there is the presence of macro-ovalocytes, hypersegmented neutrophils and megaloblasts in blood smear. Treatment should be started from the confirmation of pernicious anemia, with replacement of hydroxycobalamin or cyanocobalamin, intramuscularly or orally, always performing effective monitoring and follow-up of these patients so that they do not evolve with more serious and definitive complications. That said, with an early diagnosis and effective treatment planning with a multidisciplinary team, ensures a significant improvement in the prognosis and quality of life of these patients.